Pengaruh Penggunaan Media Digital Islami terhadap Motivasi Belajar PAI Siswa SDN 293 Aek Manyuruk - Putri Maharani; Syamsiah Depalina Siregar (PT. Willy Print Art, 2026)
This study aims to examine the influence of Islamic digital media use on the learning motivation of Islamic Religious Education (PAI) students at SDN 293 Aek Manyuruk. The development of digital technology in education provides both opportunities and challenges in shaping students’ learning behavior and spiritual awareness. This research applies a quantitative descriptive method with survey techniques, distributing questionnaires to students and interviewing PAI teachers to strengthen the data. The findings show that Islamic digital media such as learning applications, Islamic YouTube channels, online Qur’an platforms, and interactive games significantly influence students’ motivation in learning PAI. Students who actively use Islamic digital media tend to show greater enthusiasm, concentration, and consistency in studying religious materials. The results of the correlation analysis indicate a strong positive relationship between the use of Islamic digital media and students’ learning motivation, with an r-value of 0.68. This study concludes that integrating Islamic digital media in PAI lessons can create an engaging and spiritual learning atmosphere that increases students’ motivation and religious understanding. Teachers are advised to guide students in using digital media responsibly to ensure it supports, rather than distracts, their learning process.